2017
DOI: 10.1515/ipc-2017-0012
|View full text |Cite
|
Sign up to set email alerts
|

Study of Flow Behavior of Granular Material Inside Cylindrical Silo Using Ultrafast X-Ray Imaging Technique

Abstract: This paper presents an application of an ultrafast electron beam X-ray CT scanner for investigating the gravitational flow behavior of granulates through cylindrical silo model. The CT scanner allows obtaining crosssectional images of the granular material distribution with a spatial resolution of approximately 1 mm and a time resolution of 2 kHz. In order to conduct a deep analysis of the granular flow concentration changes, two image processing algorithm steps were applied. The first step deals with preproce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
(16 reference statements)
1
1
0
Order By: Relevance
“…The previous analyses of this study have shown that the concentration of particles slightly decreases as the scanning position change from top to bottom position (around 3% changes between measurements at 800 and 500 mm) (Waktola et al 2016). This is also in line with the fact that particle velocity tends to increase as the particles flow down (see Table 1).…”
Section: Investigation Of Three-dimensional Rotation Of the Particlessupporting
confidence: 90%
See 1 more Smart Citation
“…The previous analyses of this study have shown that the concentration of particles slightly decreases as the scanning position change from top to bottom position (around 3% changes between measurements at 800 and 500 mm) (Waktola et al 2016). This is also in line with the fact that particle velocity tends to increase as the particles flow down (see Table 1).…”
Section: Investigation Of Three-dimensional Rotation Of the Particlessupporting
confidence: 90%
“…The previous investigation of this study has shown that the flow analysis inside the silo model was characterized by a quasi-steady flow and particles did not change their position within few milliseconds (Waktola et al 2016). As a result, each tracer particle can be segmented individually within its own bounding area, which also helps to apply different local threshold value depending on the brightness level of the particles.…”
Section: Data Processing and Analysismentioning
confidence: 91%